2020
DOI: 10.1002/cac2.12099
|View full text |Cite
|
Sign up to set email alerts
|

The mortality of lung cancer attributable to smoking among adults in China and the United States during 1990–2017

Abstract: Background: Statistical data on the burden and relevant risk factors of lung cancer are valuable for policy-making. This study aimed to compare the mortality of lung cancer attributable to smoking stratified by sex and age among adults in China and the United States (US). Methods: We extracted age-standardized mortality rates of lung cancer during 1990-2017 using the comparative risk assessment framework of the 2017 Global Burden of Disease study. We performed an age-period-cohort analysis to estimate time tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…Our study findings showed that this increasing trend is projected to continue over the next decade. Smoking is the most important risk factor for lung cancer [10, 20, 21], contributing to approximately 75% of lung cancer‐related deaths in men and about 37% of lung cancer‐related deaths in women worldwide [20]. In the prediction period of the present study, approximately 40%–48% of lung cancer‐related deaths would be attributable to the current smoking.…”
Section: Discussionmentioning
confidence: 76%
“…Our study findings showed that this increasing trend is projected to continue over the next decade. Smoking is the most important risk factor for lung cancer [10, 20, 21], contributing to approximately 75% of lung cancer‐related deaths in men and about 37% of lung cancer‐related deaths in women worldwide [20]. In the prediction period of the present study, approximately 40%–48% of lung cancer‐related deaths would be attributable to the current smoking.…”
Section: Discussionmentioning
confidence: 76%
“…According to the findings of the China adult tobacco survey (available from http://www.chinacdc.cn/yw_9324/201905/t20190530_202932.html ), the proportion of smokers in 2018 was 26.6% overall, and 50.5% for males over 15-years-old. Moreover, the mortality of lung cancer attributable to smoking in China during 1990–2017 showed an increasing trend [ 16 ]. The situation also remains serious for alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing drug sensitivity and resistance in a neoadjuvant setting would provide useful evidence for improving treatment regimens following surgery and would benefit patients by identifying the most sensitive treatment for recurrent disease. The effectiveness of neoadjuvant treatment should be evaluated by PET/CT over time to identify unsuspected metastases and comorbidities, and to achieve smoking withdrawal [60]. Neoadjuvant treatment may shorten the length of clinical trials and accelerate the use of pCR or MPR as surrogate predictors of OS.…”
Section: Advantages and Disadvantages Of Immunotherapy As A Neoadjuvamentioning
confidence: 99%